Programming as a Development Tool of Russian Science: Evolution, Features and Application Prospects - Bilchak, Vasiliy; Nosachevskaya, Ekaterina (Olsztyn Economic Journal, 2012)
Currently, the most important preconditions for efficient development of the Russian economy include improvement of production infrastructure, use of advanced technologies and scientific support of economic processes, both nationally and in certain regions. In this connection, scientific development, the performing of fundamental and applied research, activation of innovative activity of Russian enterprises and integration of science and production have become the most relevant issues. As it is proved in practice, programming is an efficient tools for management of sectorial processes and may be effectively applied in coordination of the development of scientific processes in a certain territory. Aspects of programming evolution and the peculiarities and prospects of the use of this toolset under modern economic conditions are considered in this article, along with recommendations for improvement of management of Russian scientific and research activity. The authors also designed an algorithm for a scientific and research activity development program at the regional level that produces a systemic vision of the conditions necessary for implementation of scientific and innovative potential of the development of the economy of a certain territory. This algorithm produces a detailed understanding of the conditions necessary for implementation of the scientific and innovative potential of the development of a regional economy. Moreover, this algorithm assists in forming an efficient toolset for management of scientific and research activity and improving the competitiveness of the territorial economy.